2010
DOI: 10.1093/mutage/geq038
|View full text |Cite
|
Sign up to set email alerts
|

European eel (Anguilla anguilla) genotoxic and pro-oxidant responses following short-term exposure to Roundup(R)--a glyphosate-based herbicide

Abstract: The glyphosate-based herbicide, Roundup, is among the most used pesticides worldwide. Due to its extensive use, it has been widely detected in aquatic ecosystems representing a potential threat to non-target organisms, including fish. Despite the negative impact of this commercial formulation in fish, as described in literature, the scarcity of studies assessing its genotoxicity and underlying mechanisms is evident. Therefore, as a novel approach, this study evaluated the genotoxic potential of Roundup to bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 40 publications
2
57
0
6
Order By: Relevance
“…Cytotoxicity by oxidative stress by Roundup R has been shown by transcriptomic profiling in carp and zebrafish (Uren Webster and Santos, 2015;Sulukan et al, 2017). Acute toxicity, harmful physiological effects including hepatotoxicity, neurotoxicity, deteriorated sperm counts, early life stage development and DNA-damaging effects have been reported for numerous other fish species as well for sublethal exposures to Roundup R products including Roundup Original R , Roundup Transorb R and Roundup WG R , Garlon R , and other glyphosate-based herbicides (Soso et al, 2007;Cavalcante et al, 2008;Guilherme et al, 2010Guilherme et al, , 2014aModesto and Martinez, 2010;Shiogiri et al, 2012;Ghisi and Cestari, 2013;Nwani et al, 2013;Marques et al, 2014;Moreno et al, 2014;Navarro and Martinez, 2014;Richard et al, 2014;Sinhorin et al, 2014;Braz-Mota et al, 2015;Menéndez-Helman et al, 2015;Li et al, 2016;de Moura et al, 2017;Sánchez et al, 2017;Gonçalves et al, 2018;Zebral et al, 2018) or POEA (Yusof et al, 2014). Roundup R was found to disrupt 17β-estradiol and reduce glutathione concentration in the liver of the endangered fish species delta smelt (Hypomesus transpacificus) upon 6 h of exposure at levels corresponding to 78 µg/l glyphosate concentrations and above (Jin et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Cytotoxicity by oxidative stress by Roundup R has been shown by transcriptomic profiling in carp and zebrafish (Uren Webster and Santos, 2015;Sulukan et al, 2017). Acute toxicity, harmful physiological effects including hepatotoxicity, neurotoxicity, deteriorated sperm counts, early life stage development and DNA-damaging effects have been reported for numerous other fish species as well for sublethal exposures to Roundup R products including Roundup Original R , Roundup Transorb R and Roundup WG R , Garlon R , and other glyphosate-based herbicides (Soso et al, 2007;Cavalcante et al, 2008;Guilherme et al, 2010Guilherme et al, , 2014aModesto and Martinez, 2010;Shiogiri et al, 2012;Ghisi and Cestari, 2013;Nwani et al, 2013;Marques et al, 2014;Moreno et al, 2014;Navarro and Martinez, 2014;Richard et al, 2014;Sinhorin et al, 2014;Braz-Mota et al, 2015;Menéndez-Helman et al, 2015;Li et al, 2016;de Moura et al, 2017;Sánchez et al, 2017;Gonçalves et al, 2018;Zebral et al, 2018) or POEA (Yusof et al, 2014). Roundup R was found to disrupt 17β-estradiol and reduce glutathione concentration in the liver of the endangered fish species delta smelt (Hypomesus transpacificus) upon 6 h of exposure at levels corresponding to 78 µg/l glyphosate concentrations and above (Jin et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…They found a sixfold increase in a genetic damage indicator (GDI) in erythrocytes, using the "comet" assay method. Similarly, the comet assay applied to goldfish erythrocytes revealed DNA damage following exposure to glyphosate [42], and studies on exposure of eels to realistic concentrations of Roundup and the principal individual components, glyphosate and the surfactant polyethoxylated amine (POEA) in isolation, confirmed DNA damage in erythrocytes [43,44].…”
Section: Evidence Of Dna Damage From the Research Literaturementioning
confidence: 91%
“…Laboratory studies involving exposures to 58 and 116 µg L −1 glyphosate for 1 and 3 days have identified DNA damage in long-lived freshwater eels [120,121] and a New Zealand study found that the synergistic effects of glyphosate (exposure rate 360 µg L −1 for 26 days) and parasitic infections significantly affected the survival of a juvenile stage of native fish species (Galaxias anomalus) [122]. Further research is needed to assess the sub-lethal, long-term effects of glyphosate at rates used under forest operational conditions and to separate glyphosate effects from those of any other additives commonly used in forests.…”
Section: Indirect Effectsmentioning
confidence: 99%